A systematic review of catching and comparing the most valuable gamification elements used in online learning - Ashwaq Munif Almutairi (Edelweiss Applied Science and Technology, 2024)
Learning through games has exploded worldwide. Many students enjoy learning through gaming programs, and its effects on curricula and instruction have recently increased. Saleem et al. (2022) recommended further research to investigate the most valuable elements of gamified online learning empirically. Thus, this study systematically explored the gamified elements employed in online learning literature, focusing on identifying the most practical and valuable elements and aiming to provide insights that contribute to the existing knowledge of gaming techniques in online education.